Evaluating the failure to bloom in dark-cutting and lactate-enhanced beef longissimus steaks. (February 2022) - Ramanathan, Ranjith; Mancini, Richard A.; Konda, Murali R.; Bailey, Keith; More, Sunil; Mafi, Gretchen G.
Abstract: Previous studies have noted lower L* (lightness) values for both dark-cutting beef and normal-pH beef enhanced with lactate. In the current study, absorption-coefficient, scattering-coefficient, CIE L*a*b* values, refractive index of sarcoplasm, and inter-muscle bundle space were evaluated for dark-cutting beef, normal-pH beef enhanced with lactate, normal-pH beef enhanced with water, and normal-pH beef not enhanced with either water or lactate. Compared with non-enhanced loins, lactate-enhancement had lower a*, chroma, oxymyoglobin, reflectance, scattering, and inter-muscle bundle space as well as greater absorption and refractive index. Dark-cutting steaks had lower a*, chroma, oxymyoglobin values, reflectance, and scattering as well as less inter-muscle bundle space compared with lactate-enhanced steaks. Sarcoplasm refractive index values were greater in lactate-enhanced steaks than dark-cutting steaks. The results suggest that changes in muscle structure and optical properties due to either pH or lactate addition can alter muscle darkening and blooming properties. Highlights: Compared failure to bloom in dark-cutting and lactate-enhanced steaks Dark-cutting steaks had lower reflectance than lactate-enhanced Lactate-enhanced had greater refractive index values than dark-cutting steaks